PENGARUH TERAPI REBUSAN AIR DAUN SALAM TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MURUNG PUDAK - Ramadhani, Aprida; Meldawati, Meldawati; Ariani, Malisa (Jurnal Anestesi, 2024)
Hypertension is a dangerous disease, especially if it occurs in women who are pregnant. Management of hypertension in pregnancy one with nonpharmacology, namely bay leaves can also be used for traditional medicine for the treatment of blood pressure. The purpose of the study was to determine the effect of bay leaf water decoction therapy on reducing blood pressure in pregnant women in the Murung Pudak Health Center Work Area. The research method used pseudo-experiments (Quasi Experimental Design) with a pretest-posttest design with control group design using two types of treatment, with a total sample of 34 people with porpusive sampling side techniques. The results of the study found that blood pressure in the treatment group decreased in systolic and diastolic pressure, blood pressure in the control group did not decrease in systolic and diastolic, blood pressure in the treatment group was obtained 20.74 while in the control group a mean rank of 14.26 was obtained and there was an effect of bay leaf water decoction therapy on reducing blood pressure in pregnant women in the work area of the Murung Pudak Health Center, with p-value = 0.048 (p-value < 0.05).